Culture matters for life history trade-offs. (2017) - Wiessner, Polly
Abstract: Van Lange et al. add important life history perspectives to understanding violence. However, direct links between climate and violence are unlikely because cultural institutions modify human responses. Examples are given from the Bushmen of the Kalahari and Enga of Papua New Guinea. The correlations identified may occur because many countries closer to the equator are caught in the gap between the demise of traditional cultural institutions and the rise of modern forms of governance.